HUBUNGAN INTENSITAS MEROKOK DENGAN MOTIVASI BELAJAR SISWA SMK MIGAS TEKNOLOGI RIAU PEKANBARU - Tanisa Mega Silvia; Arneliwati Arneliwati; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Smoking intensity is defined as the average number of cigarettes smoked per day which a substance is burned and the resulting smoke breathed in to be tasted. Adolescent smoking can foster cognitive decline and negative health consequences. The purpose of this study is to identify smoking intensity and its relation to student’s academic achievement at SMK Migas Technology Riau, Pekanbaru. This study is a descriptive correlation study. A crosssectional design is used to examine data from 80 respondents on the first grade. With total population sampling technique, researcher chooses a modified questionnaire sheet that has been tested for reliability and validity as research instrument. Involving bivariate and univariate analysis, Chi-Square statistical test is also used to see if there is a relationship between two variables. The results demonstrate that there is no significant relationship between smoking intensity and student’s motivation to learn with P Value (0,319) > α (0,05). Desired change is expected to happen in all community members, especially adolescent smokers to control their smoking behaviors in order to better their academic performance.    Keywords: Adolescent, Learning Motivation, Smoking Intensity